Kredit Biogas: Mendorong Ekonomi Hijau di Koperasi Produsen Susu X - Savitri Dewi, Lely (Koaliansi : Cooperative Journal, 2025)
This research is motivated by the problem of environmental pollution due to livestock manure waste and dependence on fossil fuels. Dairy Producers Cooperative X seeks to overcome this problem through a biogas credit program. This study aims to analyze the biogas credit procedures of Dairy Producers Cooperative X and the potential economic benefits for its dairy cattle breeder members. The research method uses a quantitative and qualitative approach, collecting primary data through interviews and secondary data from the Dairy Producers Cooperative X Annual Member Meeting (RAT) reports. The results showed that the biogas credit procedure of Dairy Producers Cooperative X is simple and without collateral, with the requirement of owning a minimum of three cows and adequate land. The utilization of biogas has the potential to reduce the cost of purchasing LPG and to produce bio-slurry as a marketable organic fertilizer. In conclusion, the biogas credit of Dairy Producers Cooperative X is effective in promoting a green economy among dairy cattle breeders. This research recommends increasing socialization and assistance to members to maximize the utilization of biogas and bio-slurry, as well as the need for periodic evaluation of the credit program to ensure its sustainability and effectiveness.